2006
DOI: 10.1002/joc.1292
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for influence of anthropogenic surface processes on lower tropospheric and surface temperature trends

Abstract: In de Laat and Maurellis (2004), a new framework was introduced in the form of a spatial-thresholding trend technique for analyzing the correlation between anthropogenic surface processes (e.g. changes in land use, albedo, soil moisture, groundwater levels, solar absorption by soot or energy consumption) and lower tropospheric and surface temperature trends for the period 1979-2001. In situ measured surface and satellite-measured lower tropospheric temperature trends were shown to be higher in the vicinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…On the other hand, both dust and biomass burning aerosols may impact the surface albedo when deposited on snow; soot in particular has large impacts on absorption of radiation (Qian et al, 2011). Flanner et al (2009) applied a range of models and observations to explore the impacts of these processes on springtime climate and found that equilibrium climate experiments suggest that fossil fuel and biofuel emissions of black carbon plus organic matter (BC + OM) induce 95 % as much as springtime snow cover loss over Eurasia as anthropogenic carbon dioxide, a consequence of strong snow feedback and large BC + OM emissions from Asia. Qian et al (2009) reported that BC mixed with snow resulted in a 0.5-3 % perturbation in the snow albedo and that the snow skin (2-m air) temperature increased by 0.2-1.4 • C (0.1-1.0 • C) over the majority of snow-covered areas in the western US during late winter to early spring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, both dust and biomass burning aerosols may impact the surface albedo when deposited on snow; soot in particular has large impacts on absorption of radiation (Qian et al, 2011). Flanner et al (2009) applied a range of models and observations to explore the impacts of these processes on springtime climate and found that equilibrium climate experiments suggest that fossil fuel and biofuel emissions of black carbon plus organic matter (BC + OM) induce 95 % as much as springtime snow cover loss over Eurasia as anthropogenic carbon dioxide, a consequence of strong snow feedback and large BC + OM emissions from Asia. Qian et al (2009) reported that BC mixed with snow resulted in a 0.5-3 % perturbation in the snow albedo and that the snow skin (2-m air) temperature increased by 0.2-1.4 • C (0.1-1.0 • C) over the majority of snow-covered areas in the western US during late winter to early spring.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Wallace et al (1995Wallace et al ( , 1996, greenhouse gases are not the only factor influencing temperature variability, dynamic causes also play important roles. Geographical patterns of warming trends over land are also strongly correlated with geographical patterns of industrial and socioeconomic development (McKitrick and Michaels, 2004;De Laat and Maurellis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the causes and impacts of the UHI effect (e.g. Rydin 1992, Pearlmutter & Berliner 1998, Brazel et al 2000, Stone & Rogers 2001, Baker et al 2002, Kalnay & Cai 2003, Christy et al 2006, De Laat & Maurellis 2006. A wide range of causes have been implicated, including land surface energy balance (or imbalance) due to urbanized land surface and built structures, anthropogenic heat release and different atmospheric constituents over the city (Landsberg 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent papers (de Laat and Maurellis, 2006;McKitrick and Michaels, 2007) (henceforth dLM06 and MM07) have independently asserted that records of surface warming are likely contaminated due to 'anthropogenic surface processes'. This could be interpreted as either asserting that the 'contamination' is an artifact and the surface records, therefore, give a misleading picture of 'true' global warming, or that unaccounted-for processes need to be incorporated into climate model hindcasts.…”
Section: Introductionmentioning
confidence: 99%